Optimization of Motion Estimation Algorithm Based on FPGA Hardware System and Video Tracking - Jin, Shujiao; Jin, Hu (Microprocessors and microsystems, 2021)
Motion Estimation (ME) is a computationally expensive step in video tracking. A thorough search technique produces the best execution time and the best accuracy. Computational burden, many fast search algorithms limit and report the number of places to search. Motion estimation, analysis of image sequences, computer vision, tracking a target, and is a critical process in a wide range of fields and applications such as video coding. Precision motion estimation lowers significantly bit rate, but can require a complexity of higher computational. This is different reference frames, sub-pixel estimation, and video compression standards, including techniques such as variable block size, MPEG, especially true for a new generation. Only the motion estimation in H.261 is limited to an integer pixel accuracy, rather than the pixel grid, not in the object is often located, move to move between pixels. The system proposed in the motion vector optimization motion estimation (OME) pixel accuracy. By estimating the amount of displacement at a finer resolution, improve prediction, it can expect better performance than motion estimation using an integer pixel precision. Optimization motion estimation (OME) and the compensation method is very similar to that employed in other standards. The main is that block-based motion estimation and compensation is suitable for optimization structures in MPEG-4. Motion estimation (ME) is one of the most computationally-intensive companies in the video compression technology. Video compression algorithm, MPEG1, MPEG4, such as H.261 and H.264, a lot of the standard used. Improved compression performance. Energy effective motion estimation technique is reduced to the rest of the frame involved in motion compensation.